2010
DOI: 10.1111/j.1742-6723.2010.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome mimicked by acute cholecystitis

Abstract: Various aetiologies have been reported that cause severe trauma segment and T-wave abnormalities that are not related to acute coronary syndromes. However, the reports of transient ECG abnormalities associated with acute cholecystitis are limited in the literature. We describe a 42-year-old man presented with abdominal pain and hypertensive episode that developed dynamic ECG changes mimicking acute coronary syndrome and was diagnosed acute cholecystitis eventually. Emergency physicians should keep in mind dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In previous studies, gallbladder distension has been associated with nonspecific T-wave inversions or ST segment depressions that are similar to those of ischemic heart disease [1, 2, 3, 4], and only five previous cases with similar ischemic ECG changes attributed to cholecystitis have been reported [5, 6, 7, 8, 9]. Several studies in animals [10, 11] have demonstrated that gallbladder distension can reduce coronary blood flow and increase heart rate and arterial blood pressure, and may explain the association with transiently mimicked myocardial ischemia and ST segment ECG changes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, gallbladder distension has been associated with nonspecific T-wave inversions or ST segment depressions that are similar to those of ischemic heart disease [1, 2, 3, 4], and only five previous cases with similar ischemic ECG changes attributed to cholecystitis have been reported [5, 6, 7, 8, 9]. Several studies in animals [10, 11] have demonstrated that gallbladder distension can reduce coronary blood flow and increase heart rate and arterial blood pressure, and may explain the association with transiently mimicked myocardial ischemia and ST segment ECG changes.…”
Section: Discussionmentioning
confidence: 99%
“…Visceral-cardiac reflex secondary to gastric distention which causes increased vagal tone can lead to ECG changes. Symmetrical T-wave inversions in patients with biliary pathology have been explained using this concept in several case reports [3, 4]. The increased vagal tone may also cause transient coronary vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that not only chest symptoms but also ECG changes suggestive of myocardial ischemia might be present in patients with cholecystitis, such as T-wave inversion, ST segment depression, and ST segment elevation [2, 10]. In addition to their confusing symptoms and ECG changes, H-FABP—a biochemical diagnostic marker in the early phase of acute myocardial infarction [11]—was positive in three (75 %) of four patients who were initially suspected to have acute coronary syndrome in group 1.…”
Section: Discussionmentioning
confidence: 99%
“…First, distention of the bile duct may actually reduce the coronary artery flow [16, 17]. Second, there may be a coronary vasospasm that is caused by a vagally mediated reflex [2]. ECG changes may also be evoked in response to inflammation of other visceral organs; for instance, Rubio-Tapia reported that more than half of their study patients with acute pancreatitis showed certain ECG abnormalities, some of which might reflect electrolyte alterations and dehydration [18].…”
Section: Discussionmentioning
confidence: 99%